Musculoskeletal disorders in women of childbearing age: global trends, socio-demographic disparities, and future projections - Liang Luo; Xīn Gào; Junting Yang; Xuewu Zhang; Zhike Liu; Chun Li (Annals of Medicine, 2025)
Background Musculoskeletal (MSK) disorders are a leading cause of disability worldwide, particularly prevalent among women of childbearing age (WCBA). Our aim is to comprehensively assess the global, regional, and national burden of MSK disorders in WCBA, and examine the burden of MSK disorders among WCBA at varying levels of the Socio-demographic Index (SDI), then to project the burden of these disorders through to 2045.Methods This study utilized data from the Global Burden of Disease (GBD) 2021 project, focusing on MSK disorders among WCBA (15–49 years). Age-standardized rate was calculated using the World Standard Population proportions. Descriptive analysis was conducted at global, regional, and national levels. SDI associations were explored using smoothing spline models. Projections to 2045 employed age-period-cohort models using R software.Results In 2021, the estimated global age-standardized incidence, prevalence, deaths, Years of Life Lost, Years Lived with Disability, and Disability-Adjusted Life Years (DALYs) rates per 100 000 population of MSK disorders in WCBA were 4933.9 (95% UI 3683.7–6454.4), 20145.9 (17 082.6–23 564.4), 0.7 (0.6–0.8), 40.7 (34.1–45.7), 2090.4 (1414.8–2896.2), and 2131.1 (1455.8–2936.8), respectively. From 1990 to 2021, a total of 183 countries exhibited an increase in prevalence rate and 166 countries showed an upward trend in DALYs rate. Between 1990 and 2021, there was a positive association between the SDI and age-standardized DALYs rate for MSK disorders in WCBA, both globally and regionally. By 2045, the age-standardized number of DALYs for MSK disorders in WCBA is expected to reach 48.8 million, with an age-standardized DALYs rate of 2160 per 100,000 population.Conclusion The burden of MSK disorders among WCBA is already substantial and is expected to increase further in the future. Despite the observed decline in age-standardized incidence rate of MSK disorders among WCBA in half of the regions and countries globally, the age-standardized prevalence and DALYs rates have shown an adverse increasing trend. By 2045, the global number of DALYs for MSK disorders in WCBA is projected to exceed 48 million. To mitigate the future burden of MSK disorders in WCBA, stratified and targeted healthcare strategies are essential to improve early diagnosis and treatment.